Studi Analisis Akad dan Hukum Hibah dalam Literatur Hadis Nabi - Nafisya, Zahwah Aulia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This journal discusses the hadith about grants, Grants are one form of muamalah in Islam which is based on the principle of willingness and compassion between fellow human beings. The purpose of writing this journal is to find out the meaning of grants, to find out the requirements of grants, to find out the hadiths about grants, and also to find out the law of grants. The method used in this study uses qualitative research with the type of Library Research research, namely research whose object of study uses library data in the form of books as its data source. The approach method used is a normative approach, namely an approach to Islamic teachings that views its teachings in terms of the Qur'an and hadith. The results of the study show that Islam strongly recommends giving grants as a form of social solidarity. In addition, these hadiths are an important basis in determining the law of grants in Islamic jurisprudence which continues to be relevant today.